His strength is my strategies: Experience of an English teacher in Indonesia teaching English for hyperactive students in inclusive class - NINA DESMITA; MUHAMMAD ALI MACHRUS (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: The purpose of this research was to detail how one English teacher analyzed the strengths of hyperactive students and then used those strengths to develop a strategy (role models) for teaching English to hyperactive students in a mainstream classroom.Method: This study’s information was gathered through semi-structured interviews and direct observation. The data were analyzed using a qualitative descriptive method of research. Studies have been done as a need analysis to learn the methods of teaching English to hyperactive students in an all-inclusive setting.Findings: Results showed that an English teacher not only analyzed the students’ needs (such as problem and barrier) but also in which more focused on the strengths of hyperactive students.Implications/Novel Contribution: Based on the findings of the study’s analysis of strengths, researchers were also able to draw important conclusions about how role models can be used to effectively instruct hyperactive students in English, and in particular, how to improve their speaking skills in an all-inclusive classroom setting. The positive outcome of the need analysis based on the strengths of students with Attention Deficit hyperactive Disorder (ADHD) in determining an appropriate strategy to teach English may have repercussions for students with other types of special needs in an inclusive classroom environment.